THE EFFECT OF FIRM’S PROFITABILITY, AND OTHER FACTORS ON TAX AVOIDANCE - KHALISHAH DUTA; DEBORA DEBORA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this research is to gather empirical evidence on the effect of firm profitability, firm size, firm leverage, institutional ownership, financial distress capital intensity, audit quality, CEO tenure on tax avoidance. The population used for this research are all manufacturing companies listed in the Indonesia Stock Exchange (IDX) over three-year period from 2021-2023. The sample was selected using multiple regression and purposive sampling method with the total 195 data collected. The result of this research showed capital intensity have positive effect on tax avoidance. Other independent variables such as firm profitability, firm size, firm leverage, institutional ownership, financial distress, audit quality, and ceo tenure have no effect on tax avoidance.